Unveiling the dual role of circulating tumor cells in colorectal cancer immunotherapy: a comprehensive review of biomarker utility and immune microenvironment crosstalk - Feng, Yifan; Liu, Gang; Cai, Qixue; Zhou, Jianping (Frontiers in Immunology, 2025)
Colorectal cancer (CRC) has the highest incidence in the Asia-Pacific region, accounting for 51.8% of global cases. Despite early screening methods like colonoscopy, CT, and MRI, 20-25% of patients are diagnosed at advanced stages, with some having liver metastasis. Personalized treatments, including targeted and immunotherapy, are crucial for metastatic or recurrent CRC. Circulating tumor cells (CTC), emerging as a non-invasive biomarker, play a key role in assessing metastasis and prognosis. CTC count is linked to CRC stage, microsatellite instability (MSI-H), and drug resistance, and is valuable in evaluating the response to immune checkpoint inhibitors (ICIs). Immune cells in the tumor microenvironment influence CTC behavior, impacting metastasis, immune evasion, and resistance. Advances in CTC detection and genetic markers offer new possibilities for early diagnosis and personalized treatment.